OPTIMASI KINERJA SISTEM DRAINASE MENGGUNAKAN DRAINASE RAMAH LINGKUNGAN - Praharseno, Fikri; Wicaksono, Teguh Mulyo; Widoanindyawati, Vemi (Politeknik Negeri Semarang, 2024)
The threat of flood disasters when the rainy season arrives is a big problem currently being faced by the city of Jakarta. The city of Jakarta, which is the nation's capital, has made this city a business center and metropolitan city, so that development of both structures and infrastructure is growing rapidly, as a result of this large amount of development, this will automatically reduce the availability of open land, resulting in less and less rainwater infiltration over time. In addition, rainwater as a source of clean water has been considered wastewater which can cause gloves and must be channeled downstream as quickly as possible so that rainwater is not given the opportunity to seep into the soil through infiltration and percolation processes which are conditions This will have an impact on the availability of water on land becoming less. Based on the problems above, a method is needed to optimize drainage performance in order to overcome flooding and the scarcity of water sources. One of them is using a sustainable drainage concept. This concept aims to reduce inundation due to surface flow and conserve water. The research method used was a survey, data analysis using hydrological and hydraulic analysis. The research case study was carried out at the Central Jakarta State Secretariat housing complex with the results of the analysis of the implementation of 30 infiltration wells with a diameter of 0.8 meters and a well depth of 2.4 meters. From the research results, it was found that one infiltration well can hold 1.2063 m3 of water and the well filling time is 51 seconds. So for 30 wells the reduced rainwater discharge is 36.189 m3 during 51 seconds of rain, while the planned flood discharge during 51 seconds of rain is 38.25 m3 and if the percentage is calculated, the reduced rainwater reaches 94.61%.